Pelatihan dan Pemanfaatan Biopestisida Berbasis Kearifan Lokal pada Gapoktan Jali Jaya Desa Talang Jali Lampung Utara - Nyang Vania Ayuningtyas Harini; Yeyen Ilmiasari; Eko Abadi Novrimansyah; Dea Musytari Intan Irpawa; Amirah Inas Widiawati; Muhammad Naufal Al Fatin (Sentra Kekayaan Intelektual dan Publikasi Ilmiah, 2024)
Gapoktan Jali Jaya is one of the facilities for farmer activities in Talang Jali Village, North Kotabumi District, North Lampung. The use of chemical pesticides is common among farmers, especially in the Jali Jaya Gapoktan. Even though the price is expensive, farmers still use it, because the response to pests is faster. There are several alternatives to replace chemical pesticides, namely the application of Biopesticide. Studies have been carried out that natural products come from plants with groups of secondary metabolites and bioactive compounds such as phenolics, alkaloids, terpenoids and other secondary chemicals so that they can control OPT (Plant Pest Organisms). The aim of training on the manufacture and use of biopesticides is to increase public awareness of how important it is to have healthy plants, protected from pests and not damaging the environment. This service activity is carried out through evaluation, preparation, training and implementation stages. Direct training and practical methods are used in its implementation. The results of the lecturer's community service activities were that Gapoktan members, the majority of whom were farmers, were very enthusiastic about taking part in the training and making biopesticides and participated in the activities until completion. Participants also helped practice making biopesticides using choppers and putting the ingredients into drums. Farmers' knowledge increased about biopesticide applications and 50% of participants used biopesticides to protect cultivated plants from pest attacks, especially insects.